The relationship between belief in a just world and learning burnout in Chinese junior high school students: a moderated mediation model - Wang, Xiaodi; Wei, Xuefeng; Zhang, Xue; Zou, Yuying; Zhang, Kai (Frontiers in Psychology, 2025)
We proposed a moderated mediation model to investigate the relationship between belief in a just world and learning burnout (LB) in junior high school students, as well as the mediating effect of perceived discrimination and the moderating effect of self-efficacy. A total of 797 students (399 boys and 398 girls; age ranged from 11 to 15 years old, mean age was 13.3, SD was 1.61) from Shandong province, China, completed the Belief in a Just World Scale, Questionnaire of Perceived Discrimination, General Self-Efficacy Scale, and Learning Burnout Scale. SPSS 23.0 and PROCESS macro 4.1 (Model 7) were used to test the moderated mediation model. The findings of this study proved that belief in a just world was significantly and negatively related to LB, and perceived discrimination played a mediating role between them. Self-efficacy moderated the mediating path, the effect being weaker for students with a high level of self-efficacy. These findings demonstrated that perceived discrimination is the critical link between belief in a just world and LB, and high self-efficacy helps prevent perceived discrimination and LB.